The fabrication of In2O3 toruloid nanotubes and their room temperature gas sensing properties for H2S. (25th September 2017) - Duan, Haojie; Yan, Lei; He, Yue; Li, Haiying; Liu, Li; Cheng, Yali; Du, Liting
Abstract: In2 O3 nanofibers (NFs) and toruloid nanotubes (TNTs) were fabricated by conventional electrospinning process and their sensing properties toward H2 S gas were researched. Thermogravimetric analysis, x-ray diffractometry, energy dispersive spectroscopy and scanning electron microscopy were carefully used to investigate the structures, chemical compositions and morphologies of these samples. The novel structure (TNTs) first used nonpolar mineral oil as the control agent of morphology, and the principle of forming toruloid nanotubes was studied. Phase separation plays a critical role in the process of forming toruloid nanotubes structure automatically. The new application of phase separation provided a simple and effective approach for controlling structure. The research indicated that thin-walled toruloid nanotubes showed higher responses toward H2 S compared to nanofibers or thick-walled toruloid nanotubes. Additionally, their excellent selectivity can be attributed to the special gas-sensing mechanism of In2 O3 for H2 S.